Stability in the underlying constructs of self-control - Diamond, Brie (Crime & delinquency, 2017)
The stability of self-control represents a recently popular empirical topic; however, little attention has been paid to the stability of the underlying constructs of Gottfredson and Hirschi’s conception of self-control. The present study uses longitudinal data on youth residing in the northeastern United States and employs trajectory analysis to explore the presence of varying developmental trends in these constructs. The findings indicate that these constructs follow unique and varied trajectories that may help to elucidate issues with our understanding of the stability of self-control.